The Impact of CEO Status Diffusion on the Economic Outcomes of Other Senior Managers - Graffin, Scott D.; Wade, James B.; Porac, Joseph F.; McNamee, Robert C. (Organization Science, 2008)
In this paper we develop and test predictions regarding the impact of CEO status on the economic outcomes of top management team members. Using a unique data set incorporating Financial World's widely publicized CEO of the Year contest, we found that non-CEO top management team members received higher pay when they worked for a high-status CEO. However, star CEOs themselves retained most of the compensation benefits. We also show that there is a “burden of celebrity” in that the above relationships were contingent on how well a firm performs. Last, we found that, when compared with the subordinates of less-celebrated CEOs, members of top management teams who worked for star CEOs were more likely to become CEOs themselves through internal or external promotions.